Concrete with treated bamboo reinforcement in beam / Nurul Jannah Roslan and Sallehan Ismail - Roslan, Nurul Jannah; Ismail, Sallehan (2023)
This paper focuses on concrete with treated bamboo reinforcement. It was produced due to the inflated cost of steel reinforcement bars, which use lots of energy to produce the steel reinforcement and expose lots of carbon dioxide to the atmosphere. The aim of this research is to produce concrete with treated bamboo reinforcement in beam as an innovative technology in construction with low cost and use the renewable materials. The objectives of this research are to assemble the prototype from improvised materials of concrete with treated bamboo reinforcement in beam, study its performance, and assess its marketability potential. The methodology involved in this research is data collection from the previous studies.